The Role Playing Method on the Reading Ability of Elementary School Students - Oppy Eria Trisnawati; Achmad Fathoni (Jurnal Ilmiah Sekolah Dasar, 2023)
Reading is the most common learning difficulty experienced by elementary school students in the early or lower grades. Early-grade elementary school students have significant problems related to reading and language skills. It impacts the reading ability scores of Grade 2 elementary school students, which are still low, so new methods are needed to improve student's reading skills. This study aimed to analyze the role-playing method's use on the reading ability of Grade 2 elementary school students. This research is a type of experimental research. This study used a pre-experimental research method with a one-group pretest-posttest design (pretest test-posttest single group). The subjects in this study were all 2nd-grade elementary school students, totaling 32 students consisting of 13 girls and 19 boys. The methods used to collect data are observation and tests. The instrument used is a matter of difficulty. Data analysis techniques using inferential statistical analysis. The result of the study show that the role-playing method significantly improves the reading ability of grade 2 elementary students. Thus, giving the role-playing process can improve the reading ability of grade 2 elementary students.